Evaluation of Compounds Extracted from Eight Genera of Wild Mushrooms from Nigeria for Anti-cell Proliferation Activity in Vitro - Adongbede, Erute Magdalene; Aduralere, Israel Temitope (Iraqi Journal of Science, 2019)
Mushrooms have bioactive compounds that have antimicrobial, anti-cancer and antioxidant activities among other medicinal benefits. In the present study, we examined the anti-cell proliferation activities of mushrooms from eight genera obtained from the wild in Nigeria. Saccharomyces cerevisiae was used as a model organism to screen mushroom extracts for anti-cell proliferation activity. Polyphenols, high molecular weight polysaccharides and low molecular weight compounds from aqueous extracts were obtained from the test mushrooms using methanol and water respectively. The extracts were screened in vitro at different concentrations of extracts with the CyQuant cell proliferation assay. The high molecular weight polysaccharides from tested mushrooms reduced cell proliferation (96.79% inhibition in Ganoderma multipileum Ding Hou to 66.71% inhibition in Coltricia perennis (L.) Murrill at 10.00mg/ml). Percentage inhibition caused by low molecular weight compounds varied from 94.22% (Ganoderma multipileum) to 76.19% (Coltricia perennis) at 10mg/ml. Percentage of inhibition with the polyphenols varied from 94.12% (Microporus xanthopus Fr) Kuntze) to 79.82% (Coltricia perennis) at high doses. High molecular polysaccharides, low molecular weight compounds and polyphenols from mushrooms have anti-cancer properties. The CyQUANT assay proliferation kit was a very efficient tool for screening extracts from wild mushrooms for anti-cell proliferation activities. Medicinal mushrooms in Nigeria show a lot of promise as a reservoir for drug discovery particularly in the area of cancer research.